Biosynthesis of Gut‐Microbiota‐Derived Lantibiotics Reveals a Subgroup of S8 Family Proteases for Class III Leader Removal. (20th December 2021) - Zhang, Yingying; Hong, Zhilai; Zhou, Liang; Zhang, Zhenkun; Tang, Ting; Guo, Erpeng; Zheng, Jie; Wang, Ciji; Dai, Lei; Si, Tong; Wang, Huan
Abstract: Lanthipeptides are a group of ribosomally synthesized and post‐translationally modified peptides with diverse structural features and bioactivities. Gut‐microbiota‐derived lanthipeptides play important roles in gut homeostasis of the host. Herein, we report the discovery and biosynthesis of class III lantibiotics named amylopeptins, which are derived from the gut microbiota of Sprague‐Dawley rats and display a narrow antimicrobial spectrum. In contrast to known class III lanthipeptides, the biosynthesis of amylopeptins employs AmyP, which belongs to a subgroup of S8 family serine proteases, to remove the leader of corresponding precursor peptides in a site‐specific manner during the last step of their maturation. Overall, this study shows for the first time that S8 family proteases participate in the biosynthesis of class III lanthipeptides. Abstract : A series of rat gut‐microbiota‐derived class III lanthipeptides with moderate antimicrobial activities were discovered by genome mining. The investigation of their biosynthesis revealed a subgroup of S8 family serine proteases for the removal of class III leader peptides.